Esteróis como marcadores geoquímicos da origem da matéria orgânica em sedimentos do rio aurá(região metropolitana de Belém-PA) - AGUDELO MORALES, Jorge Hernando (Universidade Federal do Pará, 2022)
The Aurá River located in Northern Brazil, Brazilian Amazon, has been experiencing anthropogenic input from riverine communities and the Aurá landfill for many years. In this work, we assess the occurrence, sources, and distribution of six sterol markers in surface sediments of Aurá River to evaluate organic inputs in this water body. Gas chromatographytandem mass spectrometry (GC/MS/MS) was used to determine sterol compounds. The sterol markers identified, diagnostic ratios, and statistical analysis showed that Aurá River sediments presented two primary sterol sources: anthropogenic (domestic sewage and inputs from Aurá landfill) and natural sources (terrestrial higher plants). Station 1 (the closest site to the Aurá landfill) presented the highest level of contamination. Coprostanol concentrations at this station was 219.8 ng g-1.This coprostanol range indicates moderate human fecal contamination. This work demonstrated that domestic sewage pollution from riverine communities and organic matter inputs from Aurá landfill might be assumed as potential threats to environmental and human health.